Алгоритми створення, збереження та використання інформації щодо методів прогнозу в інтродукції рослин - Bulakh, Р.Е. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
The necessity of data formation for prognostication in plant introduction is discussed. The proposals of expert system development, including an information about the methods of plant adaptability prognostication are considered.